A Microbiota-Dependent Subset of Skin Macrophages Protects Against Cutaneous Bacterial Infection - Park, Young Joon; Kang, Byeong Hoon; Kim, Hyun-Jin; Oh, Ji Eun; Lee, Heung Kyu (Frontiers in Immunology, 2022)
Microbiota is essential to the development and functional maturation of the immune system, both inside and outside the gut. However, the effects of the gut microbiota on myeloid cells remote from the gut remain unclear. Both transcriptomic analyses of skin from specific-pathogen-free mice and germ-free mice was performed to identify the nature and anatomic location of myeloid cells. Type I interferon (IFN) signaling was down-regulated in the skin of germ-free mice compared to that in specific pathogen-free mice. The decrease in type I IFN signaling was closely related to the presence of microbiota presence and macrophage-specific marker CD169. The absence of CD169+ macrophages resulted in increased bacterial burden and impaired immune responses against Staphylococcus aureus skin infection. CD169+ macrophages mediated the recruitment of neutrophils and γδ T cells, and the activation of γδ T cells via interleukin (IL)-23. The absence of CD169+ macrophages diminished the number of IL-17 producing T cells, which are essential for host defense against S. aureus. Our findings demonstrate the role of the microbiota in establishment of a specific myeloid cell subset expressing CD169 in the skin and provide evidence of a specific mechanism by which this subset protects against bacterial skin infection.